(untitled) (Journal of Science and Technology, 2016)
Ceramic industries in Ghana depend on fritted materials for the composition of earthenware glazes. These materials which are imported are very costly and not easy to come by. Glass from broken bottles has been used as a substitute for frit for the composition of earthenware glazes. Chemical analysis carried out into both the green bottle and the brown bottle indicated that both could be used for the manufacture of ceramic glazes